Benzoate Synthesis from Glucose or Glycerol Using Engineered Pseudomonas taiwanensis. Issue 11 (20th August 2020) - Otto, Maike; Wynands, Benedikt; Marienhagen, Jan; Blank, Lars M.; Wierckx, Nick
Abstract: Benzoic acid is one of the most commonly used food preservatives, but currently exclusively produced in petrochemical processes. In this study, a bio‐based production pathway using an engineered strain of Pseudomonas taiwanensis is described. In a phenylalanine‐overproducing strain, bacterial and plant genes are heterologously expressed to achieve production of benzoate via a β‐oxidation pathway. Strategic disruption of the native Pseudomonas benzoate degradation pathway further allows the production of catechol and cis, cis ‐muconate. Taken together, this work demonstrates new routes for the microbial production of these industrially relevant chemicals from renewable resources. Abstract : This work describes metabolic engineering of Pseudomonas taiwanensis to produce various compounds of industrial interest from renewable resources. The expression of a synthetic pathway in a phenylalanine‐overproducing strain led to benzoate accumulation. Further exploitation of native pathways then allowed to expand the product spectrum by catechol and cis, cis ‐muconate.